Real-Time 3D Presentation System for Heterogeneous Architectural Knowledge, Case Study: Wat Sri-Chum, Sukhothai - Busayarat, Chawee; Lopkerd, Prittiporn; Suksawaddi, Varodom (Journal of Architectural/Planning Research and Studies (JARS), 2014)
Sri Chum temple in Sukhothai is an important archeological site of Thailand and one of the symbols of Sukhothai historical park. The tunnel is founded insides of the Mandapa (the temple’s central building) has significant historical and cultural values in many aspects but inaccessible for general public due to fragility of iconography and inscriptions engraved on the tunnel’s wall and ceiling. In this project, the current state of Sri Chum temple was digitized by 3D laser scanner. These collected data are used as referential information to create an enriched architectural 3D model. This model can be visualized trough virtual environment in on-line information system. System user can navigate in 3D space and observe the 3D model without damaging engraved inscriptions in real building. This system can be used as a tool to access to archeological knowledge and information related to Sri Chum temple. This includes spatial, morphological, descriptive and visual information of the temple and engraved inscriptions in the restricted tunnel. The user can interact with real-time 3D scene that links to the interior and exterior database. The developed system can be used to enrich Thai cultural, historical and architectural knowledge, as well as in sustainable tourism.